Simulation of Crystallization Evolution of Polyoxymethylene During Microinjection Molding Cycle - Siginer, D (John Wiley and Sons Ltd, 2020)
A mathematical model coupled with a numerical investigation of the evolving material properties due to thermal and flow effects and in particular the evolution of the crystallinity during the full microinjection molding cycle of poly (oxymethylene) POM is presented using a multi-scale approach. A parametric analysis is performed, including all the steps of the process using an asymmetrical stepped contracting part. The velocity and temperature fields are discussed. A parabolic distribution of the velocity across the part thickness, and a temperature rise in the thin zone toward the wall have been obtained. It is attributed to the viscous energy dissipation during the filling phase, but also to the involved characteristic times for the thermal behavior of the material. Depending on the molding conditions and the locations within the micro-part, different evolution of crystallization rates are obtained leading to at least three to five morphological layers, obtained in the same part configuration of a previously work, allowing a clear understanding of the process-material interaction. © 2019 John Wiley & Sons, Ltd.